3D Modeling and Static Analysis of Telescopic Shock Absorber Unit (International Journal of Innovative Research in Computer Science & Technology, 2022)
In this paper, we present the 3D modelling  and structural analysis of a telescopic shock absorber unit  that have been considered. A telescopic shock absorber unit  from railway wheels was used in this study. The 3D model  of a telescopic shock absorber unit consists of a cylinder,  Belleville disc, eye ball, flange models that were created with  the help of CATIA V5 software, and Finite Element Analysis  (FEA) is also carried out to find the Equivalent Von-Misses  stresses and deformations to reduce the bouncing, stability,  and improve the performance of a shock absorber unit.
Keywords: Telescopic Shock Absorber; 3D Modeling; Belleville disc; Cylinder; Flange; Eye ball; FEA; Railway